Impact of Financial Support in Fueling Business Expansion for Small Enterprises - Jamiu, Tajudeen Ade; Adeoye, Moses Adeleke (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2023)
Small enterprises play an essential role in driving economic growth and job creation. However, these businesses often need help with various challenges, including limited financial resources that hinder their ability to develop and expand. This study aims to examine the impact of financial support in driving the business expansion of small enterprises. A descriptive survey research design was used to determine the sample size of the study from a population of 520 small business enterprises, and questionnaires were administered to the entire 226 sample size through personal delivery. In contrast, quantitative techniques involving the use of descriptive and inferential statistical methods were adopted for data analysis. The study highlighted the positive impact of financial support on various aspects of business expansion. The findings show that financial support enables small businesses to invest in marketing and advertising activities, upgrade their facilities and equipment, and expand their product or service offerings. In conclusion, financial support has had a significant impact in driving business expansion for small businesses. This study provides important insights into how better access to financial resources can accelerate the growth and expansion of small businesses. This research is expected to provide essential insights into how better access to financial resources can accelerate the growth and expansion of small businesses.